What is the role of IT in innovation? A bibliometric analysis of research development in IT innovation. Issue 12 (1st December 2016) - Zhang, Xi; Chen, Hui; Wang, Weiguang; Ordóñez de Pablos, Patricia
ABSTRACT: With the wide diffusion of information technology (IT) in our daily life and work, it is clear that product innovation and service innovation have more and more connection with IT, and IT has become an important tool or component in innovation. The purpose of this paper is to provide insights into future studies pertaining to this area by investigating the research development of IT innovation using bibliometric analysis. The status of IT innovation study is analysed through citation analysis with the help of CiteSpace. Influential references, hot topics, top-tier journals and important institutes are all detected, and the intellectual structure of recent studies is also mapped in this study, and we find that research on IT innovation is mainly from two directions, innovation study group and information systems study group. Finally, we follow the logic of Nambisan [2013. "Information Technology and Product/Service Innovation: A Brief Assessment and Some Suggestions for Future Research." Journal of the Association for Information Systems 14 (4): 215–226] to explore the relationship between IT and innovation through reviewing papers in the top journals in this field. We find that most studies treat IT as an enabler of innovation. Although some recent studies try to pay attention to the role of IT as a trigger for innovation and give some rationale for the IT–innovation relationship, further studies are still required to uncover the trigger effect mechanism.